Politics, Religion, and Culture in an Anxious Age - Buell, J. author. aut Link
XVI, 201 p.
Keywords: American politics is increasingly driven by apocalyptic rhetoric. Highlighting possible adverse consequences of such politics for our freedom and quality of life, the book suggests alternative policy agendas, religious and philosophical discourses, cultural framing and modes of daily living.